Breaking into the Global Market: Strategies and Challenges of Export Risk Management for Canned Blue Swimming Crab (Portunus pelagicus) at PT. MAP Central Java, Indonesia - Widyastuti, Rida; Nostalia Suseno, Dewi Alima; Palupi, Lais Syam (Golden Ratio of Marketing and Applied Psychology of Business, 2026)
This study aims to analyze the strategies and challenges of risk management in the export marketing of canned blue swimming crab (Portunus pelagicus) at PT MAP in Central Java. The research employs a descriptive qualitative approach through surveys, direct observation, and interviews with relevant stakeholders in the company. The results identify four main risks in canned crab exports: (1) export delays due to non-compliance with FDA or SNI standards, (2) fluctuating raw material availability, (3) pure risks such as temperature instability in containers and natural disasters, and (4) payment risks including defaults and currency fluctuations. To mitigate these risks, PT MAP implements strategies such as strict quality standards (HACCP, ISO 22000), supplier diversification, real-time monitoring technology (IoT), and financial instruments like Letters of Credit (L/C) and export credit insurance. The findings underscore the importance of proactive and adaptive risk management in response to global market dynamics and provide recommendations for the fisheries industry to enhance competitiveness through international certifications and multidisciplinary collaboration.